Improving creativity and collaboration through padlet-assisted project-based learning in civic education - Nova Novita; Maria Montessori; Fatmariza Fatmariza; Junaidi Indrawadi (Global Econedu, 2026)
This study aimed to improve students’ creativity and collaboration through the implementation of Project-Based Learning (PjBL) assisted by the Padlet application in Civic Education (PPKn) learning. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of planning, acting, observing, and reflecting stages. The research was conducted in three cycles involving Grade X students at SMA Negeri 8 Padang. Data were collected through observations, interviews, documentation, and project assessment rubrics measuring creativity and collaboration. The findings showed a continuous improvement in students’ creativity and collaboration across the research cycles. Creativity increased from 45.59% in the pre-action stage to 88.60% in Cycle III, while collaboration improved from 36.76% to 83.00%. The integration of PjBL and Padlet encouraged active participation, idea generation, teamwork, and meaningful learning experiences. PjBL assisted by Padlet effectively enhanced students’ creativity and collaboration in Civic Education learning.